MENINGKATKAN KEMAMPUAN MEMBACA PERMULAANDENGAN MENGGUNAKAN METODE SAS SISWA DI SDN 115 KAB. PINRANG - Gusri, Gusri (LPPM IAIN Parepare, 2015)
This study entitled â€œImproving Literacy Starters with Method Using SAS students of SD Negeri 15 PangsidSidenrengRappangâ€. The initial idea of this study because of the low ability to read the beginning of the students, especially the students are not able to read combining letters into words, words into sentences and students are not able to read aloud. The problem of this study is (a) How is improved reading skills using SAS starters graders ISDN 115 Kab. Pinrang? (B) How is the increased ability to read the beginning of the first grade students of SDN 115 Kab.Pinrang. This research is a class act who repeated cycle / cycle, that includes planning, implementation, observation, and ferleksi. This research data is data activity and student learning outcomes Early reading. Data obtained by observation and tests. The results showed that there was a significant increase, either in the activity of teachers and students at the beginning of the reading activities. The improvement can be seen in every cycle. Cycle one qualifying Less (K), two qualifying cycles Fair (C), a cycle of three qualifiers Good (B).